Structural evolution of a crustal-scale shear zone through a decreasing temperature regime: The Yukon River shear zone, Yukon-Tanana terrane, Northern Cordillera - Parsons, A; Coleman, M; Ryan, J; Zagorevski, A; Joyce, N; Gibson, H; Larson, K (Geological Society of America, 2018)
We present the first detailed structural analysis of the Yukon River shear zone (YRSZ), which forms an important structural break within the Yukon-Tanana terrane of the Northern Cordillera in Yukon (Canada). The YRSZ is a NW-SE–striking shear zone that juxtaposes Mississippian orthogneiss hanging-wall rocks (Simpson Range suite) against pre-Late Devonian metasedimentary footwall rocks (Snowcap assemblage). Field and microstructural analyses, including quartz c-axis fabric investigation, indicate that the YRSZ initiated as a top-ESE mid-crustal shear zone active through a temperature range of ≥650–500 °C to ~540–440 °C. Constraints from the footwall associated with top-ESE shearing on the YRSZ at mid-crustal conditions record a decrease in deformation temperature toward the shear zone, coincident with a transition from coaxial to non-coaxial deformation and an increase in fabric intensity, strain rate, and differential stress estimates. Collectively, these spatial trends represent a classic example of a narrowing shear zone that progressively localizes and intensifies deformation as ambient temperature decreases. U-Pb zircon geochronometry of a deformed Permian orthogneiss from within the YRSZ combined with previously published thermochronometry bracket the timing of top-ESE mid-crustal shearing between 259 ± 2 Ma and 176–168 Ma, either during Late Permian–Middle Triassic metamorphism and lithospheric extension or latest Triassic–Early Jurassic metamorphism and crustal thickening. The YRSZ was subsequently reactivated as a top-WNW upper-crustal thrust fault zone during or after Early to Middle Jurassic cooling and exhumation at 176–168 Ma. This top-WNW thrusting within the YRSZ may be responsible for structural separation of Late Triassic and Early Jurassic plutonic rocks in the hanging wall of the YRSZ from Permian plutonic rocks in its footwall.